The impact of entrepreneurial Orientation and firm performance: Mediating role of open innovation, Study of furniture manufacturing companies in Malaysia - Akbar, Fazal (2022)
Entrepreneurship and innovation are topics of great interest for the scientific community, firms and for all major governments worldwide. Malaysian furniture industry play an important role in economic development and income growth. However, increasing business competition has placed Malaysian furniture companies in a vulnerable position especially by cheap furniture producing countries like Vietnam and China. Undoubtedly, their success in responding to the challenges of their business environment depends, in great part, on their strategy for engaging in entrepreneurial behaviours and openness to innovation. The aim of the study was to empirically examine entrepreneurial orientation and open innovation dimensions that can be used by owner/managers/entrepreneurs whenever deciding whether or not to introduce innovation into the Malaysian manufacturing sector. The research used mixed-method research design in a QUAN-qual context to administer survey questionnaires and interviews of furniture manufacturer’s managers and owner’s in Johor state respectively. In the quantitative strand, a purposive sampling strategy was used to administer questionnaires to a total of 150 furniture firms’ owner/managers in Johor state. A total of 82 questionnaires were finally used in the analysis. The low response rate was due to the Covid-19 pandemic, however according to GPower sampling measures these response were adequate. Using a purposive case sampling strategy, a total of 5 furniture firm’s managers/owners were purposefully selected from three different locations in Johor Malaysia to participate in the interview. The quantitative data was analysed using Statistical Package for Social Science (SPSS) and Partial Least Squares Structural Equation Modelling Software, SmartPLS 3.2.6. The qualitative data was coded, categorised and then later analysed through Thematic Network Analysis. The research findings strengthens understanding of the EO and IO concept and their relations to firm performance within a context to those reported in prior studies. The R-square value for firm performance reached 0.409, for inbound innovation 0.308, and for outbound innovation were 0.268, accordingly. Even then, the overall R-square value for firm performance is 0.409, implying that the study's independent variables can demonstrate 40.9 percent of the variance in firm performance. Independent entrepreneurial orientation constructs can describe 30.8 percent of inbound innovation variance and 26.8 percent of outbound innovation heterogeneity. The study’s empirical findings provide the basis for recommendations for furniture industry in enhancing their EO and IO for policy-makers to design entrepreneurship and innovation support programs and initiatives for the industry.